Poly(adenine) DNA-Templated Gold Nanocluster-Based Fluorescent Strategy for the Determination of Thiol-Containing Pharmaceuticals. (22nd September 2019) - Wang, Hai-Bo; Bai, Hong-Yu; Mao, An-Li; Liu, Yan-Ming
Abstract: The fluorescence intensity of poly(adenine) DNA-templated gold nanoclusters was shown to be significantly quenched by N-acetylcysteine through the formation of the Au-S metal-ligand bonds. On the basis of the fluorescence quenching phenomenon, a sensitive, turn-off, and label-free fluorescence method has been designed for the determination of thiol-containing pharmaceuticals using poly(adenine) DNA-templated gold nanoclusters as fluorescent probes. The assay exhibited sensitive determination of N-acetylcysteine with a linear dynamic range from 10 nM to 10 μM and a limit of detection of 3 nM. Furthermore, the proposed strategy was successfully applied for the determination of N-acetylcysteine levels in acetylcysteine granule samples. Thus, the method could provide a sensitive, simple, and rapid fluorescent sensing platform for the determination of thiol-containing pharmaceuticals.